Correlation between Serum Zinc Levels and Levodopa in Parkinson’s Disease - Hirofumi Matsuyama (MDPI AG, 2021)
Long-term intake of potential zinc-chelating drugs may cause zinc deficiency. We postulated that zinc deficiency in Parkinson’s disease (PD) patients was related to the intake of drugs such as levodopa. We investigated the relationship between zinc levels and levodopa administration period, dosage, and symptoms of zinc deficiency in PD patients. We measured serum zinc levels and analyzed correlations between serum zinc levels, the levodopa oral administration period, dosage, dosing frequency, and zinc deficiency symptoms including taste disorders. Data analyses were performed using Spearman’s rank correlation coefficient. The mean serum zinc level was 60.5 ± 11.6 μg/dL. The mean administration period for levodopa was 8.0 ± 5.5 years, mean administration frequency 3.4 ± 0.9 times/d, and mean administration dose 420.6 ± 237.1 mg/d. Negative correlations between zinc levels and levodopa dosage and dosing frequency were found. Multiple regression analysis showed a significant correlation with the frequency of levodopa (β = −0.360, p = 0.007). No significant change in clinical symptoms was observed after zinc administration, but anxiety tended to improve. Our results indicated that frequent levodopa administration strongly influenced serum zinc levels which may have alleviating effects on psychiatric symptoms; therefore, preventing zinc deficiency can be important during PD treatment.